Water Requirement and Irrigation Scheduling at Kenana Sugarcane Plantation - Muataz Shareif M. Ali; Mukhtar Ahmed Mustafa; Abdallah A. Siddig (Agricultural Sciences: Techniques and Innovations Vol. 2, 2025)
Kenana Estate is one of the six scattered complexes of sugarcane established in the hot, dry environment of central Sudan. Sugar cane is an important cash crop for the production of sugar and other secondary products. Irrigation practices in Kenana have been subjected to many changes from establishment to the present day. The objective of this study was to find out an ideal indenting of irrigation schedule, based on different categories of sugarcane-crop water requirement for different areas. This study was conducted at the sugarcane fields of Kenana Estate, Sudan, in the long furrow irrigation system established in a montmorillonitic clay soil, during the two successive seasons 2000 and 2001. Since the sugarcane planting is a continuous process before and during harvesting, the cane plant and ratoon crop were divided into different categories. Kenana soil is a vertisol, which is mainly an alluvial sediment of the Blue Nile, derived mostly from the basic igneous rocks of the Ethiopian Highlands. The crop water requirement (CWR) was calculated based on the study of reference evapotranspiration (ETo), using the Penman-Monteith Approach and the CROPWATT Software. The net crop water requirement is the amount of water needed to supplement the effective rainfall in the crop root zone which has been used in the study. ETo of the same month was used with different monthly crop coefficients (kc) to get the net crop water requirement (NCWR) for 5 categories of plant cane (Oct.-, Nov.-, Dec.-, Jan.- and Feb.-planting) and 6 categories of ratoons (Nov.-, Dec.-, Jan.-, Feb.-, Mar.- and April-ratooning) based on planting dates. This indicates that in all categories of plant cane and ratoon crop of 2000 and 2001, the monthly NCWR were low in the first months of initial stage, and increased with crop development until it reached its maximum in boom stage (4,5,6 and 7months of crop age), particularly, if it is coincided by hot summer months (March and April) then declined to a minimum in the rainy months from July to September and increased again after end of rains, in both seasons the highest and lowest net crop water requirements (NCWR) were recorded in March and July respectively. Generally, when grouping the months of the two growing seasons to A (Oct. – Feb.), B (March – June) and C (July – Sept.) group, Group A represent the months of seasons overlapping which has high NCWR, however group B which represent the dry summer months, has the highest NCWR, then group C (rainy months) has the lowest NCWR. The study concluded that the group of months of the two successive seasons shows a clear trend of variation in the season overlapping months.